Consumo de gorduras em pacientes com risco cardiovascular - Pimentel, Jéssica Bastos (2016)
The objective was to evaluate intake of total fat and the presence of clinical and metabolic factors in patients with CVD risk factors. Cross-sectional study with patients of both sexes and between 30-74 years old, subjected to coronary angiography. The study was approved by CEP/HUOL/UFRN, CAAE No 0001.0.051.294-11, accomplished between June and October/2015. It was collected biodemographical, clinical, anthropometric, lifestyle and diet data. The total sample was of 51 patients, average age 56.84 (9.77) years, and predominantly male (60,8%). It registered a high frequency of hypertension (40%) in the total sample, as well as overweight (29,04kg/m²), increased waist circumference (95,03cm), and serum glucose changes (117,28mg/dL), HDL-c (37,04mg/dL) and triglycerides (TGL) (mg/dL). Total fat and AGP consumption was observed as recommended, consumption of AGS and AGM above and consumption of omega-3 and 6-source foods below that recommended. It was concluded that the population in study presents high risk for CVD, registered for inappropriate dietary intake of AGS, AGM, and omega 3 and 6 source foods, in addition to significant clinical, anthropometric and biochemical changes.